Acute Psychosis in Withdrawal from Nicotine Vaping in a Young Man with Comorbid Diabetic Ketoacidosis and Cannabis Use - Kyle J. Rutledge; Dianne L. Plath (Case Reports in Psychiatry)
Electronic delivery of nicotine, also termed “vaping,” has a growing evidence base suggesting potential harm through both exposure and withdrawal effects. The current report presents the case of a young man with multiple medical comorbidities, including insulin-dependent diabetes mellitus on an insulin pump and presumed Gilbert’s disease, and chronic cannabis use who experienced acute agitation with hallucinations in the context of quitting his vape pen “cold turkey” or abruptly discontinuing use without a nicotine replacement. While undergoing hospitalization for his complaint of nausea and vomiting in the context of euglycemic diabetic ketoacidosis and cannabis use, his psychotic symptoms became evident and continued until beginning a nicotine replacement patch. A few months later, the patient returned to the hospital again for nausea and vomiting in the context of euglycemic diabetic ketoacidosis and reported cannabis use, however this time without psychosis, and notably after resuming and continuing use of e-cigarette with nicotine replacement delivered on admission. This is the first reported case of acute psychosis related to abrupt vaping withdrawal and adds to the plethora of information regarding potential risks associated with electronic cigarette use.